European states and their Muslim citizens the impact of institutions on perceptions and boundaries - Bowen, John R.; Bertossi, Christophe; Duyvendak, Jan Willem; Krook, Mona Lena (Cambridge studies in law and society, 2014)
This book responds to the often loud debates about the place of Muslims in Western Europe by proposing an analysis based in institutions, including schools, courts, hospitals, the military, electoral politics, the labor market, and civic education courses. These studies shed light on how Muslims encounter particular faces and facets of the state as they go about their lives, seeking help and legitimacy as new citizens of a fast-changing Europe.